The Implementation of Using Google Assistant to Improve Students Speaking' Skill in SD Kusuma Bhakti Semarang: Penelitian - Dewi Lidiyawati; Faiza Hawa; T. Sri Suwarti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The background that drives this research is to improve speaking skills in 4th grade students at Kusuma Bhakti Elementary School Semarang. The purpose of this study is to determine the speaking ability of students before and after using google assistant whether there is a significant improvement. Based on the results of the study, the frequency of students who pronounced ”car” from 50 students who answered incorrectly was reduced to 21 students who answered incorrectly. In the pronunciation of Bicycle, the frequency of students who answered correctly was 39 and after treatment increased to 64. In the pronunciation of “bus”, there were 37 students who pronounced it correctly and after the treatment it increased to 55 students who pronounced it correctly. In “train” there were 28 students who answered correctly and after the treatment there were 62 correct students. Finally, “airplane” there were 30 students who pronounced correctly before treatment and after treatment there were 55 correct ones. The results of the Mc Nemar Test analysis conducted using SPSS showed a significance value of 0.000 in the pronunciation of “car” “bicycle” “train” and “airplane”, while in “bus” the significance value was 0.010. Based on (Fauzia, 2020) it can be concluded that the significance value is less than 0.05. So this study shows the effect of the implementation of goggle assistance in learning on improving students' speaking ability